(untitled) (Research, Society and Development, 2022)
This study aimed to verify the effect of butaphosphan combined with cyanocobalamin (B+C) on dry matter intake (DMI) and milk yield in high producing dairy cows. Eighteen multiparous Holstein cows managed in a compost barn system were enrolled on a calving date and remained under observation until 28 days in milk (DIM). The B+C group administered at 2500 mg of butaphosphan and 1.25 mg of cyanocobalamin (25 mL/cow/day, n = 9), or the control group (NaCl 0.9% administered at 25 mL/cow/day, n = 9,) receiving injections at calving, and at day 3 and 7 post-partum. The DMI, feed efficiency, and DMI/% body weight were evaluated until 21 DIM and the milk yield, rumination, activity, and lying time until 28 DIM. Various metabolites were evaluated at 0, 3, 7, 14, 21, and 28 DIM. DMI did not change with treatment. Milk yield was more significant in the B+C group than in the control group, with an increase of 3.66 kg/milk/d. The maintenance of DMI and the greater milk yield in the B+C group may suggest that the use of B+C can improve feed efficiency. No treatment effect was observed for concentrations of serum glucose, NEFA, BHB, and acetone, however, albumin was higher in B+C than in control. No effect was observed on milk composition. Our results suggest that B+C improves milk yield and feed efficiency by modulating the DMI.